COORDINATION STATE AND AGGREGATION PROCESS OF BACTERIOCHLOROPHYLL A AND ITS DERIVATIVES : STUDY ON ACETONE-WATER AND METHANOL-WATER SOLVENTS - Heriyanto Heriyanto; Suryasatriya Trihandaru; Leenawaty Limantara (Universitas Gadjah Mada, 2009)
Research on bacteriochlorophyll (BChl) a and its derivatives had been conducted to determine the coordination state and the aggregation process in acetone-water and methanol-water. The results showed that there were mainly two absorption peaks in BChl a and its derivatives, namely: Qx and Qy that were very sensitive to coordination state and aggregation process. The coordination state of pigment could be determined based on Qx absorption peak that was influenced by solvents. In addition, the donor number (DN) and taft parameters (β and π*) from each sovents could also be used to determine the coordination state. One or two of axial coordination toward center metal of BChl a and its derivatives have to be filled by donor electron as a foreign nucleophile. Mg-BChl was exist as five-coordinate complexes in acetone but as six-coordinate complexes in methanol. Five-coordinate complexes of Zn-BChl was occurred either in acetone or methanol. Cu-BChl was exist as four-coordinate complexes in acetone but altered to five-coordinate complexes in methanol. The agregation process was influenced by the existence of water added in pigment solution. The order of Mg-BChl a and its derivatives abilities to form new aggregate in acetone-water and methanol-water, in regard of water-addition percentage was as follow: Cu-BChl > Zn-BChl > Mg-BChl. Methanol was the solvent that could form aggregate of Mg-BChl and its derivatives at lower water-addition percentage compared to acetone.